Negative electrode-free sodium metal battery and its modified diaphragm, preparation and application of modified diaphragm

By sputtering a composite nanomaterial modified layer on the separator without anode sodium metal battery, the problem of sodium dendrites penetrating the separator is solved, and a high-performance sodium metal battery is achieved, with excellent cycle stability and safety.

CN119275493BActive Publication Date: 2025-04-22SHANTOU DONGFENG PRINTING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411807878.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-22
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The separator of the negative-electrode-free sodium metal battery needs to overcome the safety problem of the more prominent sodium dendrites growing and then penetrate the separator, causing the battery to be short-circuited and fired, and it is difficult to adapt to the high-side load positive electrode to obtain high-performance batteries.

Method used

A modified nanomaterial layer without adhesive is sputtered on the base film, including nanomaterials such as titanium nitride, zinc nitride, gallium nitride, etc., to form a modified separator to improve the conduction of sodium ions and the nucleation and deposition uniformity of sodium metals.

Benefits of technology

The nucleation and growth behavior of sodium is improved, and excellent performances such as high surface load, high current, long cycle stability are obtained, which reduces the possibility of sodium dendrites penetrating the diaphragm and improves the safety and circulation efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275493B_ABST
    Figure CN119275493B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of negative electrode-free battery systems, and specifically relates to a negative electrode-free sodium metal battery and its modified diaphragm, the preparation and application of the modified diaphragm, wherein the modified diaphragm is composed of a base film and a modified layer without a binder compounded on its surface by a sputtering method, and the modified layer includes at least one nanomaterial of titanium nitride, zinc nitride, and gallium nitride. The present invention innovatively compounds a modified layer formed by the composite of the nanomaterials without a binder on the base film, and based on the joint control of the structure and the type of nanomaterials, synergy can be achieved, and the conduction of sodium ions can be effectively induced. In addition, it is also beneficial to improve the nucleation and deposition uniformity of sodium metal. Studies have also shown that the innovative application of the modified diaphragm to the negative electrode-free sodium metal battery system can improve the nucleation and growth behavior of sodium and obtain excellent long-cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium metal batteries, and particularly relates to a sodium metal battery without a negative electrode. Background Art

[0002] With the gradual expansion of the application of lithium-ion battery technology in markets such as consumer electronics, electric vehicles, and energy storage, the problem of insufficient lithium resources has begun to emerge. Sodium-based batteries have gradually attracted attention due to the high abundance of sodium elements on Earth, and they have an important strategic position in application fields with high cost requirements such as energy storage. However, due to problems such as the still relatively low specific capacity of sodium-ion batteries, the large-scale application of sodium-ion batteries is restricted.

[0003] A battery without a negative electrode has no sodium ion insertion material on the negative electrode side, only a negative electrode current collector, and can operate as a sodium metal battery after the initial charging process, thereby providing a higher working voltage and significantly improving the volumetric energy density and mass energy density due to the reduction in the volume and weight of the battery. However, compared with an electrode with a negative electrode active material, the battery separator of a sodium metal battery without a negative electrode needs to overcome more prominent sodium dendrite growth and then penetrate the separator, causing safety problems such as battery short circuit and fire. Therefore, how to design a separator that can resist dendrites, has good cycle stability, and can regulate uniform sodium deposition / stripping is very crucial for the industrialization of sodium metal batteries without a negative electrode.

[0004] However, for sodium metal batteries without a negative electrode, the prior art has no targeted diaphragm improvement means, and its diaphragm mainly still uses the diaphragm of a conventional battery. For example, the Chinese patent document with the publication number CN118281223A discloses a sodium-based dual-ion battery without a negative electrode and its preparation method, and the specifically recorded diaphragm is a porous polymer film or a glass fiber diaphragm. Another example is that the Chinese patent document with the publication number CN118352605A discloses a sodium secondary battery, a battery module, a battery pack, and an electrical device using the same, and the recorded diaphragm includes at least two layers of second diaphragms. The first electrolyte and the second electrolyte are respectively infiltrated on different layers of the second diaphragms. The second diaphragm includes at least one of a polyethylene film, a polypropylene film, and a glass fiber film. The added volumes V of the first electrolyte and the second electrolyte per unit capacity are 3 μL / mAh < V < 10 μL / mAh. Another example is that the Chinese patent document with the publication number CN118281223A discloses a sodium-based dual-ion battery without a negative electrode and its preparation method, and the specifically recorded diaphragm is selected from a porous polymer film or a glass fiber diaphragm.

[0005] In summary, there are still few improvement schemes for the diaphragm of sodium metal batteries without a negative electrode in the prior art. Summary of the Invention

[0006] In response to the problems faced by the existing negative electrode-free battery diaphragms, the first inventive object of the present invention is to provide a modified negative electrode-free sodium metal battery diaphragm, aiming to provide a modified diaphragm that is adapted to the application requirements of negative electrode-free batteries and has excellent ionic conductivity, cycle stability, mechanical strength and other properties.

[0007] The second object of the present invention is to provide a method for preparing the modified diaphragm and its application in a negative electrode-free sodium metal battery.

[0008] The present invention also provides a negative electrode-free sodium metal battery comprising the modified diaphragm.

[0009] Compared with conventional battery separators, the battery separators of negative electrode-free sodium metal batteries have greater sodium dendrites penetrating the separator and causing battery short circuit safety hazards. It is more difficult to assemble with high-surface-loaded positive electrodes to obtain high-performance negative electrode-free batteries. In view of the problems faced by battery separators of negative electrode-free sodium metal batteries, the present invention has conducted in-depth research and provides the following improvement solutions:

[0010] To achieve the above purpose, the present invention adopts the following technical solutions:

[0011] A modified diaphragm for a negative electrode-free sodium metal battery consists of a base film and a modified layer without a binder compounded on the surface thereof by a sputtering method, wherein the modified layer comprises at least one nano material of titanium nitride, zinc nitride and gallium nitride.

[0012] In response to the problems faced by negative electrode-free sodium metal batteries, the present invention innovatively sputters a modified layer formed by the composite of the nanomaterial without a binder on the base film. Based on the joint control of the structure and the type of nanomaterial, synergy can be achieved, which can effectively induce the conduction of sodium ions. In addition, it is also beneficial to improve the nucleation and deposition uniformity of sodium metal. The study also shows that the innovative application of the modified diaphragm to the negative electrode-free sodium metal battery system can improve the nucleation and growth behavior of sodium, and obtain excellent high surface load, high current, long cycle stability and other performances.

[0013] In the present invention, the nanomaterial in the modified layer can be one of titanium nitride, zinc nitride, and gallium nitride, or a combination of two or more thereof. Further preferably, the nanomaterial comprises gallium nitride. The present invention has shown that the use of the preferred gallium nitride can further enhance the performance of the material in the negative electrode-free sodium metal battery, especially can improve the performance of the negative electrode-free sodium metal battery with a high surface positive electrode.

[0014] Preferably, in the modified layer, the nanomaterial further comprises an auxiliary nanomaterial, wherein the auxiliary nanomaterial comprises at least one of silicon nitride and boron nitride; wherein the auxiliary nanomaterial and the nanomaterial are formed on the base film by a dual-target co-sputtering method. The present invention also shows that the preferred combined modified layer material, and the co-sputtering formation method, can further synergistically assist in optimizing the sodium conduction and homogenized deposition effect of the negative electrode-free sodium metal battery, and can further enhance the electrochemical performance of the modified diaphragm in the negative electrode-free sodium metal battery.

[0015] In the present invention, the particle size of the nanomaterial can be 10 to 1000 nm.

[0016] In the present invention, the thickness of the modified layer is less than or equal to 30 μm, preferably 5 to 30 μm, and further 10 to 20 μm.

[0017] In the present invention, the base membrane may be any diaphragm material used in conventional battery systems, for example, it may be at least one of a PP diaphragm, a PE diaphragm, a PP / PE composite diaphragm, and a glass fiber diaphragm.

[0018] The present invention also provides a method for preparing the modified diaphragm, wherein the modified layer is formed on the base film by a sputtering method to obtain the modified diaphragm.

[0019] In response to the application problem of negative electrode-free sodium metal batteries, the innovative research of the present invention shows that the modified layer is formed on the surface of the base film by the sputtering method. Based on the combination of the modified layer material and the sputtering method, the adaptation effect of the prepared material to the negative electrode-free sodium metal battery can be improved, which helps to further improve the application performance of the prepared modified diaphragm in the negative electrode-free sodium metal battery.

[0020] The preparation method described in the present invention can use the base film as the substrate and the source material of the modified layer (at least one of titanium nitride, zinc nitride, and gallium nitride) as the target material for sputtering, thereby forming a nanomaterial layer on the base film, and then preparing the modified diaphragm.

[0021] Preferably, when the modified layer contains the nanomaterial and the auxiliary nanomaterial, a dual-target co-sputtering method is used to form the modified layer on the base film. The present invention also shows that when the source material is a preferred combination of raw materials, the use of dual-target co-sputtering can achieve and enhance the synergistic effect, which helps to further enhance the application performance of the prepared modified diaphragm in a negative electrode-free sodium metal battery.

[0022] In the present invention, the sputtering power is 100-500 W, and can further be 250-350 W; more preferably, it is 280-320 W.

[0023] Preferably, the sputtering time is 5 to 60 min, further 10 to 30 min, further 18 to 22 min.

[0024] The present invention also provides an application of the modified diaphragm, which is used to prepare a negative electrode-free sodium metal battery.

[0025] The application of the present invention can form a battery cell of a sodium metal battery without a negative electrode by sequentially compounding a positive electrode, a modified separator and a current collector, wherein the modified layer of the modified separator is arranged near the current collector side.

[0026] In the present invention, the positive electrode can be an electrode that is well known in the industry and can be applied to sodium metal batteries. For example, it can include a positive electrode current collector and a positive electrode material composited on its surface, and the positive electrode material includes a positive electrode active material, a binder and a conductive agent. The positive electrode active material can be any positive electrode active material containing sodium, for example, it can be at least one of sodium iron phosphate, sodium iron pyrophosphate, sodium iron pyrophosphate, sodium iron vanadium pyrophosphate, layered oxide positive electrode, etc. The current collector can be a conventional negative electrode current collector, for example, it can be copper foil or carbon-coated aluminum foil.

[0027] The present invention also provides a negative electrode-free sodium metal battery, comprising a battery cell of a positive electrode, a modified diaphragm and a current collector which are composited in sequence, wherein the modified diaphragm is the modified diaphragm described in the present invention, and the modified layer of the modified diaphragm is arranged on the side facing the current collector.

[0028] The negative electrode-free sodium metal battery of the present invention, in addition to comprising the modified separator of the present invention, other components and physicochemical structural relationships can be conventional.

[0029] Beneficial Effects

[0030] The present invention innovatively provides a modified diaphragm with completely new physical and chemical characteristics, and provides a preparation method based on the modified layer material and sputtering method. In addition, the present invention also innovatively includes the application of the modified diaphragm in a negative electrode-free sodium metal battery system.

[0031] The research of the present invention shows that the modified diaphragm obtained by the physicochemical characteristics and preparation method can help solve the problems such as uneven sodium nucleation and deposition faced by negative electrode-free sodium metal batteries in negative electrode-free sodium metal batteries.

[0032] The modified diaphragm of the present invention can reduce the problem of sodium dendrites growing through the diaphragm during the subsequent sodium deposition process, thereby causing a short circuit in the battery and causing a safety hazard; in addition, it can provide more sodium ion fast transmission channels, induce sodium ion diffusion and uniform nucleation, and improve the reversibility of sodium deposition and stripping, thereby further reducing the possibility of sodium dendrites growing through the diaphragm, and improving the safety and cycle efficiency of the negative electrode-free sodium metal battery. In particular, it can improve the performance of high-surface-loaded positive electrode-free sodium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a SEM image of the PP diaphragm base film of Example 1;

[0034] Figure 2 This is a SEM image of the surface of the modified diaphragm after sputtering coating in Example 1. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention. Based on the implementation of the present invention, other embodiments obtained by those skilled in the art without creative labor are all within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment prepares a negative electrode-free sodium metal battery separator, and the specific preparation method includes the following steps:

[0038] The dried PP diaphragm (thickness 16 μm) was placed in a magnetron sputtering device and a modified material target (titanium nitride target in this case) was used in an argon protective atmosphere for 10 -5 kPa pressure, using a working power of 300 W for sputtering for 20 minutes to obtain the modified diaphragm.

[0039] SEM images of the diaphragm before and after sputtering are shown in Figure 2. Figure 1-Figure 2 As shown, the sputtered diaphragm is evenly covered with a layer of nanoparticles, which is a binder-free coating (thickness is 300±20nm).

[0040] Performance Testing

[0041] In order to verify the performance of the prepared negative electrode-free sodium metal battery separator, the inventors used the following negative electrode-free sodium metal battery separators to assemble a negative electrode-free sodium metal battery, and then tested the performance of the obtained negative electrode-free sodium metal battery to examine the performance of the negative electrode-free sodium metal battery current collector. Specifically including:

[0042] Sodium / / modified diaphragm / / current collector half-cell: Use a cutting machine to cut the prepared negative electrode-free sodium metal battery current collector into samples with a diameter of 14 mm as the negative electrode current collector (the negative electrode current collector is uniformly made of carbon-coated aluminum foil, with the carbon layer facing the positive electrode), and assemble the half-cell using the sodium sheet as the counter electrode.

[0043] NFPP positive electrode / / modified diaphragm / / current collector Full cell: Assemble the cell with sodium iron pyrophosphate (NFPP) as the positive electrode (the material composition ratio of the positive electrode material is NFPP: conductive carbon black: PVDF = 9:1:1), 1M NaFP6 / diethylene glycol dimethyl ether (DEGDME) as the electrolyte (also as the electrolyte of the half-cell), and the modified diaphragm as the battery diaphragm (the modified layer (sputtered material layer) is on the current collector side), and 2032 button cells are assembled in a glove box (high-purity argon atmosphere, in which the oxygen and water content is less than 0.1 ppm). Then the full cell is loaded with NFPP at 16 mg cm -2 Under the load of 100mA·g -1 , 200mA·g -1 、300mA·g -1 The full cell was tested at a current density of 1 mA·cm -2 -1mAh·cm -2 , 2mA·cm -2 -1mAh·cm -2 、3mA·cm -2 -1mAh·cm -2 The test was carried out under the test conditions (the test temperature was 30℃).

[0044] Example 2

[0045] Compared with Example 1, the only difference is that the sputtering working power is changed, and the other process conditions and the process used are the same as Example 1. The experimental groups are divided into:

[0046] Group A: sputtering power is 100W, and sputtering time is 30min;

[0047] Group B: sputtering working power is 350W;

[0048] Group C: sputtering power is 500W, and sputtering time is 10min;

[0049] The performance test was carried out according to the method of Example 1. The results are shown in Table 1.

[0050] Example 3

[0051] Compared with Example 1, the only difference is that the type of modified target material is changed, and the other preparation conditions and power are the same as those of Example 1. The experimental groups are:

[0052] Group A: The modified material target is zinc nitride;

[0053] Group B: The modified material target is gallium nitride;

[0054] The performance test was carried out according to the method of Example 1. The results are shown in Table 1.

[0055] Embodiment 4 (co-sputtering scheme):

[0056] Compared with Example 1, the only difference is that dual target materials are used for co-sputtering, the sputtering time is changed to 10 minutes, and other preparation conditions and powers are the same as those in Example 1. The experimental groups are:

[0057] Group A: Sputtering targets are silicon nitride target and titanium nitride target;

[0058] Group B: Sputtering targets are silicon nitride target and zinc nitride target;

[0059] Group C: Sputtering targets are silicon nitride and gallium nitride;

[0060] Group D: Sputtering targets are boron nitride target and zinc nitride target;

[0061] The performance test was carried out according to the method of Example 1. The results are shown in Table 1.

[0062] Example 5

[0063] Compared with Example 4A, the only difference is that the dual-target co-sputtering method is not adopted. Instead, titanium nitride is sputtered first and then silicon nitride is sputtered. The single sputtering conditions are consistent with those of Example 4A.

[0064] Comparative Example 1

[0065] Compared with Example 1, the only difference is that the unmodified PP separator is directly used as the battery separator, and the performance test is carried out according to the method of Example 1. The results are shown in Table 1.

[0066] Comparative Example 2

[0067] Compared with Example 1, the only difference is that without using magnetron sputtering equipment, a total amount of 1g of nano titanium nitride (same as Example 1) powder and PVDF (ratio of 0.95:0.05) are directly ground evenly, and then added to 2ml of N-methylpyrrolidone, and then evenly coated on the PP diaphragm using a 10μm scraper, and vacuum dried in a vacuum drying oven at 80°C for 24h to obtain the diaphragm, and the performance test is carried out according to the method of Example 1. The results are shown in Table 1.

[0068] Comparative Example 3

[0069] Compared with Example 1, the only difference is that the modified material target is replaced with silicon nitride, and the other operations and parameters are the same as Example 1.

[0070] Comparative Example 4

[0071] Compared with Example 1, the only difference is that the modified material target is replaced with boron nitride, and the other operations and parameters are the same as Example 1.

[0072]

[0073] It can be seen from Table 1 that compounding the binder-free modified layer on the base film and further coordinating the joint control of the materials can significantly enhance its performance in the negative electrode-free battery system, for example, significantly improve its cycle performance, especially the cycle performance under high current. In addition, it can be seen from Examples 1 and 3 that the nanomaterial is gallium nitride, which can further enhance the performance of the material. In addition, it can be seen from Examples 1, 4 and 5 that the use of the combined target material and the method of dual-target co-sputtering can obtain a material that is more suitable for the requirements of a negative electrode-free battery and can show better performance. In particular, the use of dual-target co-sputtering containing gallium nitride can obtain better negative electrode-free battery performance.

[0074] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A sodium metal battery without a negative electrode, comprising a battery cell of a positive electrode, a modified separator and a current collector which are sequentially composited, characterized in that: The modified diaphragm is composed of a base film and a binder-free modified layer compounded on the surface thereof by a sputtering method; The modified layer includes at least one nanomaterial selected from titanium nitride, zinc nitride, and gallium nitride, and further includes an auxiliary nanomaterial, wherein the auxiliary nanomaterial includes at least one nanomaterial selected from silicon nitride and boron nitride; wherein the auxiliary nanomaterial and the nanomaterial are formed on the base film by a dual-target co-sputtering method; The sputtering power is 100~500 W; the sputtering time is 5~60 min; The modified layer of the modified separator is arranged on the side close to the current collector.

2. The negative electrode-free sodium metal battery according to claim 1, characterized in that: The base film is at least one of a PP diaphragm, a PE diaphragm, a PP / PE composite diaphragm, and a glass fiber diaphragm.

3. The negative electrode-free sodium metal battery according to claim 1, characterized in that: The sputtering power is 250~350W.

4. The negative electrode-free sodium metal battery according to claim 1, characterized in that: The sputtering time is 10~30min.

Citation Information

Patent Citations

  • Negative-electrode-free sodium-based dual-ion battery and preparation method thereof

    CN118281223A

  • Sodium secondary battery, battery module, battery pack, and electric device

    CN118352605A

  • Isolating membrane, preparation method of isolating membrane, and electrochemical device comprising isolating membrane

    CN109994691A

  • Battery diaphragm capable of inhibiting growth of sodium dendrites as well as preparation method and application of battery diaphragm

    CN117977115A

  • Composite diaphragm, sodium ion battery and electric device

    CN220527133U